The impact of Prophet Muhammad motivation technique on students' performance - WanYusof, Wan Mazwati (s.n, 2012)
Research from Islamic perspective should begin from the truth of the Quran and Sunnah (Acikgenj, 1996), the main source of Islamic knowledge. From the analysis of the main source of Islamic knowledge, theories are formulated and tested. We embark on this research to formulate techniques used by Prophet Muhammad to motivate students to perform better. This study attempts to extract techniques used by the Prophet in raising his companions self-esteem and motivation to change negative behavior thus perform better and to explore and describe the impacts of these techniques on students performance. This study employed qualitative research method